RELATIONSHIP OF PHYSICAL ACTIVITY LEVELS WITH GENESIS OBESITY IN FACULTY OF MEDICINE UNIVERSITY OF RIAU GENERATION 2012 & 2013 - Utami, T. Widya Wira; Bebasari, Eka; Ernalia, Yanti (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTAccording to data from the Health Research (Riskesdas) Ministry ofHealth of the Republic of Indonesia in 2013, the prevalence of obese adolescentsaged over 18 years in the province of Riau based on measurements of body massindex (BMI) of 32%. This figure is quite high compared to the average prevalenceof obesity in Indonesia as much as 15.4%. One of the factors that affectnutritional status is physical activity. This research is analytic research with crosssectional design of the students of the Faculty of Medicine, University of RiauGeneration of 2012 and 2013. This study used questionnaires to assess the statusof the IPAQ physical activity and BMI measurements to assess nutritional status.The results from this study is that the study respondents aged 19 years had thegreatest frequency are many 78 peoples (48.1%). Most respondents were femaleas much as 132 people (81,5%). Nutritional status of most respondents is normalthat as many 88 people (54,3%). Respondents who have the nutritional status ofoverweight and obesity as many as 74 people (45,7%). The most respondent havemoderate physical activity are 81 people ( 50 % ), and who have heavy physicalactivity as much are 25 people ( 15,4%) . Based from the chi square test found nosignificant association between physical activity with obesity ( p = 0.524 ) on thestudents of the Faculty of Medicine, University of Riau generation of 2012 and2013 .Keywords: Physical Activity, Obesity, Nutritional Status, BMI